Think Aloud Videos and Assessment in an Introductory Economics Class for Undergraduate Students - Derrill D. Watson II; James Gentry (Park University, 2024)
This paper demonstrates the value of an innovative test preparation strategy, applied over multiple semesters to one principles of macroeconomics class. The professor makes a video of himself taking a copy of the test students are preparing for, talking aloud about how to think about the question and work through the solution. A natural experiment occurred one semester when the professor was unable to provide the think-aloud preparation video, but other, standard preparation materials were in place. It is demonstrated that students increase their scores on other questions in the same modules by an average of 7.6 percentage points with think-aloud videos. Think aloud interventions are shown to be an effective tool to enhance student content learning.